Il paesaggio culturale fluviale come motore di sviluppo del territorio: il caso della Valle della Loira - Verdelli, Laura (Ri-Vista. Research for landscape architecture, 2015)
After its abandoning as an infrastructural axis (transportation and economic) the Loire river middle course starts today a process of valorisation and revitalisation of its cultural and natural landscapes. According to the most recent declinations of the cultural patrimony notion a series of cultural, patrimonial and landscape infrastructures is organising following a scheme based on three major groups of actions, often overlapped and combined: actions related to cultural tourism and the attractiveness of the biggest French UNESCO’s site; actions connected with the valorisation of savoir-faire, ancient workmanships and know-how and local products (vineyards production in particular); actions associated with the high quality of live provided by the landscape and environmental context (than, more than supply a green and ecological aspect, also offers a suggestive water scenery). Heritage is taken into account as a possible factor of territorial sustainable development, through the valorisation of its different components, of identity and memorial values, as well as market ones, within an environment where river corridor concentrate multiples and, sometimes contradictories, expectations.